The Effect of Celebrity Endorsement on Purchase Intention Mediated by Brand Image: Industry and Brand Level Analysis - Viriyani Viriyani; Ansell Kevyn Sutrisno (iBuss Management, 2023)
The utilization of celebrity endorsement as a marketing strategy has gained widespread popularity across various industries, including the electronic industry. The objective of this study is to assess the effect of celebrity endorsement towards purchase intention, specifically through brand image. The analysis compares the relationship between variables at two levels: industry and brand, each at varying levels of maturity. The research analyzed Indonesian citizens who are aware of Vivo and Samsung brand and the respondents are acquired through survey generator websites, namely Populix and Survey Monkey. Using the PLS-SEM method continued by MGA (Multi Group Analysis), this research assesses the relationship among 379 valid respondents with Vivo and Samsung. Results indicate that at the industry level, brand image plays a positive mediating role in the relationship between celebrity endorsement and purchase intention, despite a negative direct relationship between the two. At the brand level, celebrity endorsement has a negative impact on purchase intention for Vivo, while exhibiting no significant effect on Samsung brand. However, brand image positively mediates the relationship between the two. Furthermore, multigroup analysis reveals that the difference in effect between the two brands is not statistically significant.Keywords: Celebrity endorsement, Purchase intention, Brand image, Smartphone industry, Indonesia.